Ethnolinguistics as a Tool for Studying the Cultural Heritage of the World’s Peoples - Polyezhayev, Yu.; Maksymova, A.; Tytar, O.; Kulichenko, A. K.; Rukolyanska, N.; Куліченко, Алла Костянтинівна (My University, 2024)
The article shows that the links between linguistic and cultural phenomena, the collaboration of ethnocultural and ethnopsychological aspects in the functioning of language can be clarified by the examples of idioms in different languages. The aim is to specify a theoretical justification of ethnolinguistic manifestations in language in different countries. The methodology used for this study was a literature review, which was focused on a systematic approach to evaluate current works and studies in the arena of ethnolinguistics. The analytical-synthetic and descriptive methods, methods of comparison and analogy, and the functional approach were used to analyse and determine the relationship between language and culture on the basis of idioms from Ukrainian, English, Chinese, Turkish and German. Ethnolinguistics studies culture through the prism of historical events, national norms, customs, rituals, traditions, folk beliefs, ethical and aesthetic values, through thematic groups of borrowed vocabulary, phraseology, and paremics. The interaction of language and culture is manifested in the mastery of various texts, in language contacts, in the development of cultural attitudes, and in interpersonal communication. The essential characteristics of national culture can be studied with the aid of proverbs or idioms from various languages that reflect their respective cultures, common or different histories, ways of thinking, religious beliefs, traditions, customs, rituals, values, lifestyles, etc., according to linguistic studies of phraseological units based on the examples of the UK, USA, China, Germany, Turkey, and Ukraine. The conclusion of this study demonstrate the possibility of comparing cultures and analysing various processes that took place in several societies, and will allow scholars to conduct further research and adequately assess cultural phenomena through language.
Keywords: Cultural Identities; Intercultural Communication; Lexical Borrowings; Phraseological Units; Language Policy; Ethnoculture; Preservation of Linguistic Diversity